New World camelids are sentinels for the presence of Borna disease virus - Malbon, Alexandra J.; Dürrwald, Ralf; Kolodziejek, Jolanta; Nowotny, Norbert; Kobera, Ralph; Pöhle, Dietrich; Muluneh, Aemero; Dervas, Eva; Cebra, Christopher; Steffen, Frank; Paternoster, Giulia; Gerspach, Christian; et al. (Transboundary and emerging diseases, 2022)
Borna disease (BD), a frequently fatal neurologic disorder caused by Borna disease virus 1 (BoDV‐1), has been observed for decades in horses, sheep, and other mammals in certain regions of Europe. The bicoloured white‐toothed shrew (Crocidura leucodon) was identified as a persistently infected species involved in virus transmission. Recently, BoDV‐1 attracted attention as a cause of fatal encephalitis in humans. Here, we report investigations on BoDV‐1‐infected llamas from a farm in a BD endemic area of Switzerland, and alpacas from holdings in a region of Germany where BD was last seen in the 1960s but not thereafter. All New World camelids showed apathy and abnormal behaviour, necessitating euthanasia. Histologically, severe non‐suppurative meningoencephalitis with neuronal Joest‐Degen inclusion bodies was observed. BoDV‐1 was confirmed by immunohistology, RT‐qPCR, and sequencing in selected animals. Analysis of the llama herd over 20 years showed that losses due to clinically suspected BD increased within the last decade. BoDV‐1 whole‐genome sequences from one Swiss llama and one German alpaca and—for comparison—from one Swiss horse and one German shrew were established. They represent the first published whole‐genome sequences of BoDV‐1 clusters 1B and 3, respectively. Our analysis suggests that New World camelids may have a role as a sentinel species for BoDV‐1 infection, even when symptomatic cases are lacking in other animal species.